Evaluating the role of aromatase inhibitors in the treatment of low-grade endometrial stromal sarcomas - Fionnuala Crowley; Karen A. Cadoo; Sarah Chiang; Diana L. Mandelker; Raazi Bajwa; Alexia Iasonos; Qin C. Zhou; Kathryn M. Miller; Martee L. Hensley; Roisin E. O'Cearbhaill (Elsevier, 2022)
Objectives: Endometrial stromal sarcomas (ESS) are rare, accounting for < 1% of all uterine malignancies. Treatment has been guided by small case series and retrospective studies. Endocrine therapy is used in both adjuvant and metastatic settings. Aromatase inhibitors (AIs) are widely used in clinical practice. We sought to evaluate clinical outcomes of AI use in the largest cohort of patients with LGESS to date. Methods: We performed a retrospective study of patients with LGESS treated with an AI at our institution from 1/1998-12/2020. Response was evaluated using RECIST 1.1. The Kaplan-Meier method was used to estimate median progression-free (PFS) and overall (OS) survival. Results: Forty patients were identified. Treatment was well tolerated, with 57.5% experiencing adverse effects. The most common were arthralgias (12 patients, 30%) and hot flashes (9, 22.5%). Two of 11 patients with RECIST-evaluable imaging experienced a partial response to treatment. Median PFS for the entire cohort was 79.2 months (95% CI 39.7 months to NE); the 5-year PFS rate was 59.6% (95% CI 41.8% to 73.6, p = 0.065). Median follow-up for the 29 survivors was 97.9 months (range: 12.6-226.7). The 5-year OS rate was 81.5% (95% CI 64.9-90.7%). One patient who discontinued AI after 10 years of treatment recurred 1 year later. Conclusion: AIs were well tolerated and offered periods of prolonged disease stability, even in the metastatic setting. Our study suggests, however, that response rates may be lower than previously reported. Data on optimal duration of treatment is needed, but the rarity of LGESS is an obstacle to conducting large clinical trials.